What Are The Most Effective First-Line Pharmacological Treatments For Managing Bullous Pemphigoid In Elderly Patients Over 65 Years Old? : A Systematic Review - Anak Agung Istri Indah Paramita; I Dewa Ayu Supriyantini; Ni Putu Devi Gema Partamayani; Natasha Caroline Gigir (The International Journal of Medical Science and Health Research, 2025)
Introduction: Bullous pemphigoid is an autoimmune blistering disease primarily affecting older adults. Managing this condition in patients over 65 is challenging, requiring a balance between controlling severe symptoms and minimizing treatment-related risks. This review synthesizes evidence on the most effective and safe first-line pharmacological treatments for this vulnerable population. Methods: A systematic review was conducted following PRISMA guidelines. We searched PubMed, Semantic Scholar, Springer, and Google Scholar for randomized controlled trials, systematic reviews, and prospective cohort studies investigating first-line pharmacological treatments for bullous pemphigoid in patients over 65. Results: Systemic corticosteroids like prednisolone offer rapid disease control (91% achieving ≤3 blisters at 6 weeks) but are associated with a high rate of severe adverse events (36% at 1 year). Doxycycline was found to be non-inferior for short-term control (74% achieving ≤3 blisters at 6 weeks) with a significantly better safety profile, halving the rate of severe adverse events to 18%. High-potency topical corticosteroids were effective and well-tolerated for moderate disease. Discussion: The evidence supports a risk-stratified approach. While effective, the high toxicity of systemic corticosteroids makes them less ideal as a universal first-line choice. Doxycycline and high-potency topical corticosteroids represent a safer initial strategy, balancing good efficacy with significantly lower risk. Novel biologics, particularly dupilumab, are poised to become a new standard of care, offering high efficacy without the severe risks of broad immunosuppression, pending results from ongoing randomized controlled trials. Conclusion: For elderly patients with bullous pemphigoid, doxycycline and high-potency topical corticosteroids are the preferred first-line treatments due to their favorable balance of efficacy and safety. Systemic corticosteroids should be reserved for specific cases where rapid control is essential and risks are manageable. Novel therapies like dupilumab show great promise and may soon redefine the standard of care, pending final evidence from ongoing trials.